Determining Factors Affecting Cooperative Membership of the Beekeepers Using Decision Tree Algorithms - Tayfun Çukur; Figen Çukur (Journal of Agricultural Sciences)
Agricultural cooperatives have important contributions to farmers. Thanks to cooperatives, agricultural products are sold at high prices, while agricultural inputs can be purchased at low prices. Cooperatives provide their partners with technical support in product processing, grading, standardization, storage and quality. On the other hand, cooperatives contribute to the sustainability of agricultural activities by providing credit support to their members. The current research was carried out Milas district of Muğla province, which is the center of pine honey production in Turkey. In the current research, a survey was conducted face to face with 62 farmers engaged in beekeeping, and the decision tree model, which is one of the data mining methods, was used in determining the factors that affect the beekeepers' membership in cooperatives. As a result of the statistical analyses conducted, it was concluded that on the cooperative membership of beekeepers, their status of using credit, education level and status of receiving beekeeping supports have a highly significant influence.